1977
DOI: 10.1017/s0043174500033452
|View full text |Cite
|
Sign up to set email alerts
|

Movement and Activity of Glyphosate in Purple Nutsedge

Abstract: Tubers from purple nutsedge (Cyperus rotundusL.) plants grown in the greenhouse for 2 to 10 weeks did not germinate after foliar applications of 4 kg/ha glyphosate (N-(phosphonomethyl)glycine). Some tubers from 12- and 24-week-old purple nutsedge plants survived glyphosate application. Translocation of14C-glyphosate from treated purple nutsedge leaves to other plant parts increased from 5% of the amount applied at 1 day to 19% at 4 days after application. Specific activity of14C in tubers was greater than in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
2
2

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 10 publications
4
42
2
2
Order By: Relevance
“…The correlation coefficient between '•'C recovery and reduction in regrowth was 0-91, We did not identify the '''C-label as intact glyphosate. However, glyphosate appears to be quite stable in the plant during the time period involved in these studies, Zandstra & Nishimoto (1977) reported no evidence of metabolism of glyphosate in purple nutsedge leaves or tubers.…”
Section: Translocation Of'''c-glyphosatementioning
confidence: 75%
“…The correlation coefficient between '•'C recovery and reduction in regrowth was 0-91, We did not identify the '''C-label as intact glyphosate. However, glyphosate appears to be quite stable in the plant during the time period involved in these studies, Zandstra & Nishimoto (1977) reported no evidence of metabolism of glyphosate in purple nutsedge leaves or tubers.…”
Section: Translocation Of'''c-glyphosatementioning
confidence: 75%
“…Necrosis occurs several days after initial symptoms and complete plant death results in 21 to 35 days depending on species and maturity/size of treated plants. Glyphosate is extremely difficult to metabolize by plants and is readily translocated to areas of new growth [114]. This stability within plant tissues is the reason it has excellent activity on many perennial plants, allowing glyphosate to be 'stored' in overwintering tissues such rhizomes and rootstocks [115].…”
Section: Glyphosatementioning
confidence: 99%
“…The range of counting efficiency was 92 to 98%, and the data listed in Table 2 were corrected for this. Because few glyphosate metabolites have been reported in plants within 48 h after treatment (Devine and Bandeen 1983;Gottrup et al 1976;Zandstra and Nishimoto 1977), the radioactivity recovered will be referred to as C-glyphosate.…”
Section: Absorption and Translocation Studymentioning
confidence: 99%